Methods of teaching folklore at secondary school (Eurasian Journal of Philology Science and Education, 2023)
Folk songs, fairy tales, riddles, and tongue twisters are important for their emotional impact on a person, and studying folklore allows you to understand better and feel the spirit of your people, their worldview, culture and history. The relevance of the study is based on the fact that at the present stage, due attention is paid to the use of folklore in the educational process at secondary school. The purpose of the study: to determine the role of folklore in the educational process due to the cross-section of knowledge at secondary schools in Kazakhstan, to highlight the main genres of folklore, and to show the main techniques and methods of teaching folklore. In clarifying this topic, comparative, descriptive, deductive and axiomatic methods, dogmatic and abstraction methods, as well as the method of analysis and synthesis were used. The result of the study was the definition of the concept of folklore and consideration of the classification of genres. The empirical part of the work consists of a survey conducted among 44 students, as well as a survey of 15 teachers of the highest category of secondary schools in Kazakhstan about the methods of teaching folklore, its impact on the upbringing of the younger generation and the activation of the educational process as. The article considers Kazakh folklore, its components, shows the model of teaching folklore at school. The study made it possible to highlight certain features and assess the prospects for further introduction of folklore teaching methods into the educational system of Kazakhstan, as well as to develop recommendations for the study of Kazakh folklore for the 5-6 grades. The practical significance of this topic is due to the main methodological aspects that affect the effectiveness of the use of certain methods of teaching folklore at secondary schools.